New Engineering Contract (NEC) 1993 as radical changes to the Malaysian standard forms of contract - Chan, Melissa Yuet Li (2006)
The construction industry in Malaysia has been plagued by the rising of claims, disputes and litigation. Design and bidding documents are seldom adequately complete prior to the tendering exercise. Hence, tender documents and conditions of contracts were tinkered in an amateurish way loading substantial amount of risk on to the Contractor. All these in turn, precipitated certain notable changes in attitude of Contractors towards cost recovery and claims. The Malaysian Construction Industry Development Board (CIDB) entrusted with the responsibility to address pertinent issues and problems faced by the industry drafted and issued the CIDB Standard Form of Contract for Building Works in year 2000. Prior to that, the Pertubuhan Arkitek Malaysia (PAM) issued a revised Standard Form of Contract in year 1998 to replace the old 1969 PAM Form that has been used for over 30 years by private sector. Of late, for the purpose to meet the needs of the Malaysian construction industry, the revised PAM Form of Contact 2006 is now at its final stage of drafting. Stakeholders and constituents of the industry are seen to be of the opinion that improved contracts or further tightened of clauses in a contract will better govern the projects and control of disputes. In line with this development in Standard Forms of Contracts in Malaysia, this research attempts to examine the possibility of implementing the New Engineering Contract (NEC) 1993 issued under the sanction of Institution of Civil Engineers (ICE), United Kingdom in the Malaysian construction industry. This study however concluded that the industry is generally not ready to embrace the NEC at this point of time. Nevertheless, the industry showed encouraging response to certain aspects of the NEC such as â€œsimple plain language contractâ€? and â€œadjudicationâ€? which could provide rooms for further development in Malaysia.